The Ethic of Access: An AIDS Activist Won Public Access to Experimental Therapies, and This Must Now Extend to Psychedelics for Mental Illness - Campbell, Morgan; Williams, Monnica T. (Frontiers in Psychiatry, 2021)
If patients with mental illnesses are to be treated fairly in comparison with other categories of patients, they must be given access to promising experimental therapies, including psychedelics. The right of early access to promising therapies was advanced as an ethical principle by activist Larry Kramer during the AIDS pandemic, and has now largely been adopted by the medical establishment. Patients are regularly granted access to experimental drugs for many illness categories, such as cancer and infectious diseases. The need for expanded access is especially relevant during evolving crises like the AIDS and the coronavirus pandemics. In contrast to non-psychiatric branches of medicine, psychiatry has failed to expedite access to promising drugs in the face of public health emergencies, psychological crises, the wishes of many patients, and the needs of the community. Psychiatry must catch up to the rest of medicine and allow the preferences of patients for access to guide policy and law regarding unapproved medications like psychedelics.